Does IT Outsourcing Increase Firm Success? An Empirical Assessment using Firm-Level Data - Jörg Ohnemus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Using German firm-level data, an endogenous switching regression model within a production function framework is estimated in order to explore differences in labor productivity between IT outsourcing and non-IT outsourcing firms. This approach takes possible complementarities between IT outsourcing and production input factors into account and further allows IT outsourcing to affect any factor of the production function. Estimation results show that IT outsourcing firms produce more efficiently than non-IT outsourcing firms. Furthermore, they have a significantly larger output elasticity with respect to computer workers. Therefore computer workers and IT outsourcing can be interpreted as complementary factors positively affecting firms? labor productivity. An additional analysis indicates that IT outsourcing, in the medium-term, has a positive effect on firms? employment growth rate.
Keywords: C21; D24; J24; J21; 330; IT Outsourcing; Productivity; Endogenous Switching Regression; Employment Growth; Datenverarbeitung; Informationstechnik; Outsourcing; Unternehmensentwicklung; Arbeitsproduktivität; Beschäftigungseffekt; Deutschland